Manipulating topological transformations of polar structures through real-time observation of the dynamic polarization evolution - K. Du (Nature Portfolio, 2019)
Direct observation of the dynamic evolution of polar domain structures at atomic level remains challenging. Here, the authors report the observation of real-time topological transformations of polar structures in PbTiO3/SrTiO3 multilayers.